1993
DOI: 10.1002/zaac.19936190108
|View full text |Cite
|
Sign up to set email alerts
|

Untersuchungen an elektronenleitenden Oxidsystemen. XXIII. Struktur und Eigenschaften stabiler Spinelle in den Reihen MzNiMn2−ZO4 (M=Li, Fe)

Abstract: Es wird über die Darstellung und Eigenschaften der Spinellverbindungen LiZNiMn2−ZO4 (0 ⩽ Z ⩽ 2/3) und FeZNiMn2−ZO4 (0 ⩽ Z ⩽ 1) berichtet und die Reihe ZnZNiMn2−ZO4 (0 ⩽ Z ⩽ 1) einbezogen. Im Unterschied zur Ausgangsverbindung NiMn2O4 (Z=0) erweisen sich die Spinelle Z ≥ 1/6 beim Tempern (400−500°C) an Luft als thermodynamisch stabil. In den Reihen mit M=Li oder Zn erfährt die obere thermodynamische Stabilitätsgrenze eine Herabsetzung, nicht dagegen in der Reihe mit M=Fe. Die Veränderungen werden strukturchemis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 23 publications
3
12
0
Order By: Relevance
“…[33]), a lattice parameter of, e.g., 816.4 pm [34] to 817.0 pm [35] are expected. As already discussed in detail for very similar materials back in 1993 by Feltz et al, [36] advocated by Cabana in the recent LNMO debate, [34,37,38] and concluded from our preceding work, [39] the higher Mn(III) content most likely is a side effect of the formation of the Ni-rich secondary phase, coming along with a Ni-depletion of the LNMO phase:…”
Section: (4 Of 14)supporting
confidence: 53%
See 1 more Smart Citation
“…[33]), a lattice parameter of, e.g., 816.4 pm [34] to 817.0 pm [35] are expected. As already discussed in detail for very similar materials back in 1993 by Feltz et al, [36] advocated by Cabana in the recent LNMO debate, [34,37,38] and concluded from our preceding work, [39] the higher Mn(III) content most likely is a side effect of the formation of the Ni-rich secondary phase, coming along with a Ni-depletion of the LNMO phase:…”
Section: (4 Of 14)supporting
confidence: 53%
“…[33]), a lattice parameter of, e.g., 816.4 pm [ 34 ] to 817.0 pm [ 35 ] are expected. As already discussed in detail for very similar materials back in 1993 by Feltz et al., [ 36 ] advocated by Cabana in the recent LNMO debate, [ 34,37,38 ] and concluded from our preceding work, [ 39 ] the higher Mn(III) content most likely is a side effect of the formation of the Ni‐rich secondary phase, coming along with a Ni‐depletion of the LNMO phase: LiNi0.5IIMn1.5IVO4LiNi0.5yIIMn1.5yIVMn2yIIIO4goodbreak+LixNi1xnormalOgoodbreak+O2\[ \begin{array}{*{20}{c}}{{\rm{LiNi}}_{0.5}^{{\rm{II}}}{\rm{Mn}}_{1.5}^{{\rm{IV}}}{{\rm{O}}_4} \rightleftharpoons {\rm{LiNi}}_{0.5 - y}^{{\rm{II}}}{\rm{Mn}}_{1.5 - y}^{{\rm{IV}}}{\rm{Mn}}_{2y}^{{\rm{III}}}{{\rm{O}}_4} + {\rm{L}}{{\rm{i}}_x}{\rm{N}}{{\rm{i}}_{1 - x}}{\rm{O}} + {{\rm{O}}_2}}\end{array} \] According to Equation (), chemical equilibrium shifts to the right side when calcination is carried out above the decomposition temperature (often referred to as the oxygen release temperature) and to the left for lower calcination temperatures. However, the back reaction may be limited by excessive phase segregation and kinetic restraint.…”
Section: Resultsmentioning
confidence: 81%
“…A distribution of Mn 3+ /Fe 3+ over the two sites was reported for cubic NiMnFeO 4 synthesized at elevated temperatures. 36,49,50 Although the occupation pattern of the sites seems to be obvious, the ratio of Mn 3+ and Fe 3+ on the tetrahedral site cannot be determined using the present experimental data. In all three spectra (Figure 6), an intense signal is observed that is due to the spin-allowed 1s → 4p transition.…”
Section: Resultsmentioning
confidence: 62%
“…We note that NiMnFeO 4 adopts cubic symmetry if the sample was prepared at higher temperatures. 36,49,50 Remarkably, a Rietveld refinement of the XRD pattern using the tetragonal model yielded no improvement of the refinement (better R value). This emphasizes that the tetragonal distortion is a local phenomenon and is averaged out into a strained yet still cubic symmetry on a global scale.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation